2017
DOI: 10.1073/pnas.1610708114
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction of US summertime ozone using statistical analysis of large scale climate patterns

Abstract: We develop a statistical model to predict June-July-August (JJA) daily maximum 8-h average (MDA8) ozone concentrations in the eastern United States based on large-scale climate patterns during the previous spring. We find that anomalously high JJA ozone in the East is correlated with these springtime patterns: warm tropical Atlantic and cold northeast Pacific sea surface temperatures (SSTs), as well as positive sea level pressure (SLP) anomalies over Hawaii and negative SLP anomalies over the Atlantic and Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…Large-scale variations in temperature, pressure, and airflow can also lead to substantial year-to-year variations in O 3 production, air mass stagnation, snowpack accumulation, and wildfire severity (Fiore et al, 2015;Mote et al, 2016;Gong et al, 2017;Jaffe and Zhang., 2017;Lin et al, 2017;Shen and Mickley, 2017). Interannual variability of surface O 3 in the Intermountain West during summer is found to correlate with wildfire severity (Jaffe, 2011;Jaffe et al, 2008).…”
Section: Interannual Variability and Trends In Baseline And Usb Omentioning
confidence: 93%
“…Large-scale variations in temperature, pressure, and airflow can also lead to substantial year-to-year variations in O 3 production, air mass stagnation, snowpack accumulation, and wildfire severity (Fiore et al, 2015;Mote et al, 2016;Gong et al, 2017;Jaffe and Zhang., 2017;Lin et al, 2017;Shen and Mickley, 2017). Interannual variability of surface O 3 in the Intermountain West during summer is found to correlate with wildfire severity (Jaffe, 2011;Jaffe et al, 2008).…”
Section: Interannual Variability and Trends In Baseline And Usb Omentioning
confidence: 93%
“…Barnes and Fiore 2013, Shen et al 2015, Otero et al 2016, teleconnection patterns (e.g. Shen and Mickley 2017), and distribution of anthropogenic precursor emissions (e.g. He et al 2013a) which have been shown to influence surface-level pollution.…”
Section: Reconciliation With Previous Studiesmentioning
confidence: 99%
“…It can be used to differentiate longitudinally isolated events and to characterize local and regional weather (Huang and Nakamura, 2016). Shen and Mickley (2017b) note the connection between the eastwardpropagating flux in wave activity associated with the Pacific extreme pattern and increased surface pressure, reduced precipitation, warmer temperatures, more frequent heat waves, and enhanced ozone over the eastern US. A diagnosis of LWA also provides a metric for the occurrence of blocking events, events associated with anomalous or extreme midlatitude weather such as heat waves Martineau et al, 2017), which have been associated with surface ozone extremes (e.g., Sun et al, 2017;Meehl et al, 2018;Phalitnonkiat et al, 2018).…”
Section: Introductionmentioning
confidence: 96%